Software copyright: fairness analysis through the parallel link between users and authors - Dakroury, Islam (AUC Knowledge Fountain, 2020)
Until lawmakers harmonize the relationship between copyright owners and users within the context of software copyright, it will remain a controversial topic within the legal field. The ongoing conflict of interests between copyright owners and users along with the increasing complexities of technology make the situation of software copyright more complicated. It is something that the doctrine of fair use/dealing aims to stabilize. In the past few decades, the doctrine of fair use/dealing has evolved towards more complex recording and sharing tools, such as the peer-to-peer networks. However, the court rulings that involve fair use/dealing in software copyright cases contain many inconsistencies. Many of these inconsistencies are caused by the continuous enforcement of software copying restrictions, which have made software copying acts that used to be fair as, instead, copyright infringements. In addition, the test that determines the fairness of copying acts contains some ambiguities. Nevertheless, fair use/dealing has achieved some balance in terms of the legal powers between copyright owners and users and to preserves, to some extent, copyright’s true purpose, which is to maintain the flow of knowledge and information through proper promotion and dissemination not only to protect the interests of copyright owners. Furthermore, cases related to software copyright prove that the law should not stand in the way of technological progress or to enact laws that impede its function. Instead, law should guide technology to a safe path that guarantees the best of interests for all parties. This paper argues that reconciling the fair use/dealing with interests of copyright owners and users should be based on examining the interaction between users and authors and its impact on the community at large instead of determining the legitimacy of the consumers’ use. This path will require a mechanism that properly weighs the needs and interests of both the copyright owners and users. A mechanism that includes contribution, alternate modes of dissemination, technological neutrality, and proportionality stricto sensu is a capable tool for such cases.